2011
DOI: 10.1016/j.bbamem.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of uric acid transporter Urat1 (Slc22a12) in rats

Abstract: Uric acid transporter URAT1 contributes significantly to reabsorption of uric acid in humans to maintain a constant serum uric acid (SUA) level. Since alteration of SUA level is associated with various diseases, it is important to clarify the mechanism of change in SUA. However, although expression of mRNA of an ortholog of URAT1 (rUrat1) in rats has been reported, functional analysis and localization have not been done. Therefore, rat rUrat1 was functionally analyzed using gene expression systems and isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Disruption of renal regulation of serum urate content is one of the pathological factors of hyperuricemia and gout. The analogous transport system in rats reveals 74% homology in amino acid sequence and has the same features and location, but a lower affinity for urate [45].…”
Section: Kidney Injury Markers In Obesitymentioning
confidence: 98%
See 3 more Smart Citations
“…Disruption of renal regulation of serum urate content is one of the pathological factors of hyperuricemia and gout. The analogous transport system in rats reveals 74% homology in amino acid sequence and has the same features and location, but a lower affinity for urate [45].…”
Section: Kidney Injury Markers In Obesitymentioning
confidence: 98%
“…About 90% of filtered urate is reabsorbed in the kidney; transport systems responsible for the reabsorption of urate in the nephron cells are found in both human and rats [36,[45][46][47]. The most important of them are URAT1 and GLUT9 [45][46][47].…”
Section: Kidney Injury Markers In Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the assay system, promoter region DNAs corresponding to unproximal tubules of the kidney, where it is responsible for the tubular reabsorption of urate (6,20,18). Kikuchi et al showed that the proximal promoter region of Slc22a12 was hypermethylated in the liver and kidney medulla, whereas this region was relatively hypomethylated in the kidney cortex (14).…”
Section: Development Of a Real-time Quantitative Pcr Assaymentioning
confidence: 99%